SARS-CoV-2 variants: Impact on biological and clinical outcome - Mahilkar, Shakuntala; Agrawal, Sachee; Chaudhary, Sakshi; Parikh, Swapneil; Sonkar, Subash C.; Verma, Dileep Kumar; Chitalia, Vidushi; Mehta, Divya; Koner, Bidhan Chandra; Vijay, Neetu; Shastri, Jayanthi; Sunil, Sujatha (Frontiers in Medicine, 2022)
The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) that was first identified in December 2019, in Wuhan, China was found to be the etiological agent for a novel respiratory infection that led to a Coronavirus Induced Disease named COVID-19. The disease spread to pandemic magnitudes within a few weeks and since then we are dealing with several waves across the world, due to the emergence of variants and novel mutations in this RNA virus. A direct outcome of these variants apart from the spike of cases is the diverse disease presentation and difficulty in employing effective diagnostic tools apart from confusing disease outcomes. Transmissibility rate of the variants, host response, and virus evolution are some of the features found to impact COVID-19 disease management. In this review, we will discuss the emerging variants of SARS-CoV-2, notable mutations in the viral genome, the possible impact of these mutations on detection, disease presentation and management as well as the recent findings in the mechanisms that underlie virus-host interaction. Our aim is to invigorate a scientific debate on how pathogenic potential of the new pandemic viral strains contributes towards development in the field of virology in general and COVID disease in particular.